Spatially Resolved Analysis of Screen Printed Photoanodes of Dye-Sensitized Solar Cells by Scanning Electrochemical Microscopy. (20th December 2016) - Schmidt, Ina; Plettenberg, Inka; Kimmich, Daniel; Ellis, Hanna; Witt, Julia; Dosche, Carsten; Wittstock, Gunther
Graphical abstract: Abstract: Different approaches are compared for imaging local differences in the performance of nanostructured dye-sensitized solar cells (DSCs) using scanning electrochemical microscopy (SECM). The DSCs were fabricated from TiO2 and the triphenylamine dye (E)-3-(5-(4-(bis(2', 4'-dibutoxy-[1, 1'-biphenyl]-4-yl)amino)phenyl)thiophen-2-yl)-2-cyanoacrylic acid, called D35. The components of the redox electrolytes cobalt trisbipyridine ([Co(bpy)3 ] 3+/2+ ) and iodide/triiodide (I ‐ /I3 − ) were used as SECM mediators. Imaging was performed by the feedback (FB) mode and the substrate-generation/tip collection (SG/TC) mode of SECM with additional options of local and temporal illumination. In FB mode, the SECM microelectrode (ME) reduces the mediator which is re-oxidized at the illuminated photoanode. In the SG/TC mode, the reduced form of the mediator is oxidized at the photoanode and the oxidized form is detected at the ME. It is expected that the SG/TC is more sensitive than the FB mode but provides lower lateral resolution. However, imaging is complicated by the strong light scattering in the nanoporous photoanode and the long residence time of charge carriers under the conditions of SECM imaging with low mediator concentrations. This prevents approaches based on local illumination or temporal illumination. Using shear force SECM (SF-SECM) in the FB mode, local differences in the morphology and performance of screen-printed photoanodes could be resolved that resulted from screen printing process. The morphological variations are also corroborated by scanning force microscopy and optical phase contrast microscopy. Furthermore, isolated irregularities were detected in which morphology and local performance were not correlated.